Spatial analysis of green space use in Tabriz metropolis, Iran - Omid Mobaraki (TeMA: Journal of Land Use, Mobility and Environment, 2023)
The growth and development of urbanization in the last few decades, as well as the land use changes around and inside big cities have been considered as one of the most essential challenges of global sustainable development. The increase in the desire for urbanization and improper management has changed the use of green spaces and gardens around and inside the cities to profitable residential and commercial uses. Accordingly, considering urban parks and green spaces and recognizing their spatial inadequacies is of utmost importance for optimal use by citizens. This research aimed to evaluate the use of green space in the city of Tabriz and the way it is distributed in the urban areas of Tabriz city. This study was an applied research, and its methodology was descriptive-analytical. Moreover, class difference limit model, cluster analysis, and GIS software were used to analyze the data. The results of the study indicated that the per capita use of green space in Tabriz city was much lower than the international and national standard, the spatial distribution of green space use was not the same in different areas of Tabriz city, and was more unbalanced. The results of the cluster analysis method showed that the regions in Tabriz city are at different levels in terms of green space indicators. The results of the class difference limit model showed that the regions of the city of Tabriz do not enjoy balanced green space, and the green space is not distributed evenly among different regions.